MOTIVASI PT. PINDAD MEMASUKI KAWASAN PASAR SENJATA DI YORDANIA TAHUN 2016-2017 - Moedhea Erzha Pratiwi; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research analyzed the motivation of PT. Pindad entering the arms market area in Jordan in 2016-2017. Jordan became a relatively stable area in the Middle East despite being among conflicting nations. Jordan is the entrance to the arms market in the Middle East. It is considered of Pindad, LCC. as an opportunity to develop the Indonesian armaments industry towards a larger international trade sector in the Middle East area.This research uses descriptive research method of analysis and historical analysis. Some of the data obtained comes from books, journals, articles, newspapers, internet and other media. In this study also uses neo liberal perspective, the theory of competitive advantage, used of international trade concepts and level of group analysis in looking at the cases studied. Pindad, LCC. as a multinational cooperation and Jordan as one of the International actors.Participation of PT.Pindad in Special Operations Forces and Exhibition held in Jordan is a big step for the Indonesian arms industry. Pindad, LCC. was able to enter the arms industry in Jordan. This is marked by a follow-up meeting between Pindad, LCC. and the Jordanian government. Cooperation relationship between Pindad, LCC. and Jordan became a new breakthrough for the marketing of products made by Pindad, LCC. to enter into the arms market area in the Middle East.Keywords: PT. Pindad, Jordan, The Arms Market.